Comparative genomic study of non-typeable Haemophilus influenzae in children with pneumonia and healthy controls - Deming Zhang; Wenjian Wang; Chunli Song; Tingting Huang; Hongyu Chen; Zihao Liu; Yiwen Zhou; Heping Wang (iScience)
Summary: Non-typeable Haemophilus influenzae (NTHi) is a common pathogen causing respiratory infections, including pneumonia in children, and can also be found in the upper respiratory tracts of asymptomatic individuals. This study examines genomic variations between NTHi strains from healthy children and those from children with acute or chronic community-acquired pneumonia (CAP). Using bacterial genome-wide association studies (bGWAS), we compared these strains to identify key differences. Our analysis revealed that approximately 32% of genes exhibit variations between commensal and pathogenic states. Notably, we identified changes in peptidoglycan biosynthesis pathways and significant virulence factors associated with pneumonia. Furthermore, we observed a significant difference in β-lactam resistance due to PBP3 mutations between the healthy and pneumonia groups, confirmed by the ampicillin susceptibility test and characterized by the mutation pattern D350N, S357N, S385T, L389F. These findings contribute valuable insights into the genomic basis of NTHi pathogenicity and may inform more targeted clinical diagnostics and treatments.